Quantitation of Selected Volatiles from Leaves and Rhizomes of Shell Ginger (Alpinia zerumbet) - Morales O., María J. (Zamorano: Escuela Agrícola Panamericana, 2020, 2020)
Shell ginger (Alpinia zerumbet) is a species native of southeastern Asia which is used as a culinary spice and as a medicinal plant. To characterize the volatiles differentially present in the leaves and rhizomes of shell ginger, the two plant materials were individually extracted using solvent and the extracts were subsequently distilled by Solvent Assisted Flavor Evaporation (SAFE). The resulting volatile isolates were then analyzed by Gas Chromatography-Mass Spectrometry (GC-MS). As a result of the GC-MS experiments, 35 volatiles where identified. To aid in the identification experiments and separate volatiles based on their polarity, SAFE isolates were fractionated into six fractions by Solid-Phase Extraction (SPE) using different solvent mixtures. Eighteen compounds were present in the non-polar eluent, five were present in the medium polarity eluent (non-polar and polar association), and eleven volatiles were resent in the polar eluent. Five volatiles including 1,8-cineole, linalool, fenchyl acetate, bornyl acetate, and trans-methyl cinnamate were selected and quantitated by GC-MS using isotopically labelled 2H32-pentadecane as an internal standard. Trans-methyl cinnamate (87.20 ppm), 1,8-cineole (70.50 ppm), and linalool (21.60 ppm) were the highest in the leaves. Fenchyl acetate (431.50 ppm) and bornyl acetate (253.40 ppm) were the highest in the rhizomes.